Pemanfaatan Tenaga Oleh RBA Terhadap ANM Ditinjau Dari Undang Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang - Edwin Horianto (SAPIENTIA ET VIRTUS, 2019)
Society often view woman as a graceful, sensitive, and patient human being. That view often found in a patriarchal society. Patriarchal society itself is a society where man had absolute power and dominence over a woman. Because of that view, woman tend to be discriminated and abuse physically, sexually, or physchologically. Human trafficking is one form of crime against woman. The Republic of Indonesia had regulated regarding the human trafficking on Law Number 21 of 2007 on Eradication of Human Trafficking. The philosophy behind the creation of this law is based on the fact that human trafficking especially on woman and children is an act that against the dignity of human and can be consider as a breach of human right, therefore it has to be eliminate. Also the current legislation regarding human trafficking isn’t capable of providing a comprehensive and integrated legal basis for the eradiction of such criminal acts. RBA as a criminal offender on this paper has fulfilled the definition of human trafficking on Article 2 of Law Number 21 of 2012, also she is eligible to bear criminal responsibility of her actions as she was legally adult and legally competent, she also intentionally perform the crime, and has no legal excuse to be excused from criminal responsibility. Through this study, we hoped that: the victims of human trafficking should be rehabilitated, and the judges should be more cautious in examining the subject matter to produce impartial verdicts.